LINGUAGENS EM MOVIMENTO E A CONTAÇÃO DE HISTÓRIAS PARA EDUCADORES E CRIANÇAS - FEIL, ISELDA S.; VARGAS, LAINE D. J.; ALLEBRANDT, LÍDIA I.; FEIL, ISELDA S.; VARGAS, LAINE D. J.; ALLEBRANDT, LÍDIA I.; FEIL, ISELDA S.; VARGAS, LAINE D. J.; ALLEBRANDT, LÍDIA I. (Salão do Conhecimento, 2013)
Resumo